2005
DOI: 10.1021/jf0506941
|View full text |Cite
|
Sign up to set email alerts
|

Haze Formation in Model Beer Systems

Abstract: The interaction of a haze-active protein (gliadin) and a haze-active polyphenol (tannic acid) was studied in a model beer system in order to investigate the principle mechanisms of haze formation at low temperatures. Low concentrations (g/L) of tannic acid, high concentrations of gliadin, and comparatively high temperatures lead to maximum haze values. When considered on a molar basis, the greatest haze levels are displayed at an approximate 1:1 equivalence of polyphenol and protein. The greater part of haze f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…From results of the haze model and apple juice, guar gum might be the most efficient polysaccharide in preventing the haze formation. In previous study, the interaction of gliadin and tannic acid was used to simulate the haze formation in beer (Miedl, Garcia, & Bamforth, 2005). However, beverages have commonly a variety of proteins and polyphenols, which could form different types of protein–polyphenol haze.…”
Section: Discussionmentioning
confidence: 99%
“…From results of the haze model and apple juice, guar gum might be the most efficient polysaccharide in preventing the haze formation. In previous study, the interaction of gliadin and tannic acid was used to simulate the haze formation in beer (Miedl, Garcia, & Bamforth, 2005). However, beverages have commonly a variety of proteins and polyphenols, which could form different types of protein–polyphenol haze.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular significance was the work of Michaela Miedl and I, in which we demonstrated that the key to precipitation of material in cold stabilisation procedures is the lowness of the temperature rather than the time of storage . We also pursued model systems to extend the seminal work of Siebert on chill haze . Other relevant research concerned the efficiency of polyphenol adsorbents , including the demonstration that PVPP has no impact on the flavour stability of beer .…”
Section: Downstream Processing and Hazementioning
confidence: 99%
“…It is well established that beer protein haze is due to interactions between proteins, derived from the barley storage protein hordein and rich in proline, and hop polyphenolic compounds (Bamforth, 1999;Siebert, 1999;Siebert and Lynn, 2003;Miedl et al, 2005). White wine proteins are not derived from storage proteins of grape seed nor are they as rich in proline as hordein.…”
Section: Protein Haze Formation In Winementioning
confidence: 99%